The management of high risk labours by midwives with advanced training - J.V. Larsen; E.J. Muller (AOSIS, 1980)
A survey undertaken in 1977' demonstrated that 53,3 percent of women delivering in a rural obstetric unit had high risk factors demanding hospital delivery. The present shortage of medical staff available in such areas demands that even patients with high risk factors must often be delivered by midwives. Midwives are however, usually trained on the understanding that all patients with significant risk factors should be delivered by medical staff, and thus